2002
DOI: 10.1034/j.1600-0501.2002.130513.x
|View full text |Cite
|
Sign up to set email alerts
|

Platelets stimulate proliferation of bone cells: involvement of platelet‐derived growth factor, microparticles and membranes

Abstract: Platelets have been implicated in accelerated bone regeneration in grafting applications. The beneficial effects of platelets may involve their ability to stimulate the proliferation of osteoblasts. We therefore determined the mitogenic response of human trabecular bone-derived cells to human platelets and supernatants of thrombin-activated platelets. We can show a approximately 50-fold increase in DNA-synthesis of bone cells (BC) cultured in the presence of platelets as determined by [3H]-thymidine incorporat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
164
2
13

Year Published

2003
2003
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 210 publications
(186 citation statements)
references
References 28 publications
7
164
2
13
Order By: Relevance
“…In line with our finding it was recently shown that unstimulated plateletrich plasma (PRP) induced bone cell proliferation while the supernatant from thrombin-activated PRP did not have any effect [46]. Filtrate and supernatant from thrombin-stimulated platelets have been shown to increase proliferation of human pulp-derived cells, bone cells and endothelial cells [44,45,47], respectively. However, the experimental setup in these studies differs substantial from our study.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…In line with our finding it was recently shown that unstimulated plateletrich plasma (PRP) induced bone cell proliferation while the supernatant from thrombin-activated PRP did not have any effect [46]. Filtrate and supernatant from thrombin-stimulated platelets have been shown to increase proliferation of human pulp-derived cells, bone cells and endothelial cells [44,45,47], respectively. However, the experimental setup in these studies differs substantial from our study.…”
Section: Discussionsupporting
confidence: 77%
“…Platelets store well characterised growth factors in their alpha granules, but interestingly we found that the platelet lysate, but not the supernatants obtained from lysed platelets, induced GP-ASMC proliferation to the same extent as the membrane preparation. In accordance, it has previously been shown that platelet membranes stimulate proliferation of coronary artery smooth muscle cells coronary artery smooth muscle cells [37], human dental pulp-derived cells [44] and bone cells [45]. However, Matsuo et al [36] found that platelet membranes do not induce growth of hepatocytes.…”
Section: Discussionmentioning
confidence: 62%
“…Bu otolog plazma zengin bir büyüme faktörü kaynağıdır ve çeşitli uygulamalarının doku onarımı ve rejenerasyonunu arttırmada etkili bir yol olduğu gösterilmistir. [11][12][13] Plateletler yaralanmış damarlara fibrinojen vasıtasıyla yapıştıklarında, pıhtılaşma işlemini başlatmak amacıyla seratonin, tromboksan ve adenozin içeren granüller salgılamaya başlarlar. Daha sonra bu çözülmez ağdan yara yerine doğru plateletler aralarında PDGF, TGF-ß ve IGF'nin en önemlileri olduğu bir dizi büyüme faktörünü salgılarlar.…”
Section: -5unclassified
“…12 Bir çalışmada, platelet membranlarının insan trabeküler kemik hücrelerinin mitojenik aktivitelerini arttırdığı ve bu sayede mineralize dokuların rejenerasyonuna katkıda bulunduğu gösterilmistir. 13 İn vivo olarak gerçekleştirilen bir çalışmada ise Aghaloo 14 ve arkadaşları tavsan kafataslarında hazırladıkları 8 mm'lik defektleri otojen kemik, yalnız basına PRP ve otojen kemik-PRP kombinasyonu ile greftlemişler, kontrol grubuna ise herhangi bir tedavi uygulamamışlardır. Defektler 1., 2. ve 4. aylarda radyografik, histolojik ve histomorfometrik olarak değerlendirilmiştir.…”
Section: -5unclassified
See 1 more Smart Citation